Improving Orientation and Mobility Abilities through Ball with Sound Media Innovation for Students with Visual Impairment - Febriana Pratiwi (Universitas Pendidikan Indonesia, 2019)
The purpose of this study was to determine the effect of voiced ball media innovation on orientation and mobility abilities in physical education learning for low vision students. The research method uses one group pre-posttest. Participants in this study were as many as 6 low vision students consisting of 3 men and 3 women, with an age range of 8-10 years. Data analysis using t-test. The results showed that the innovation of voiced ball media had a significant effect of 2.05 (α = 0.05) on the orientation and mobility abilities of low vision students. Conclusions of voiced ball media innovation help improve orientation and mobility abilities in physical education learning for low vision students. The innovation of voiced ball media can be one of the alternative media for physical education teachers in providing learning specific learning that uses ball media for students with visual impairments. AbstrakTujuan penelitian ini ialah untuk mengetahui pengaruh inovasi bola bersuara terhadap kemampuan orientasi dan mobilitas dalam pembelajaran pendidikan jasmani bagi siswa tunanetra. Metode penelitian menggunakan one group pre-posttest. Partisipan dalam penelitian ini yaitu sebanyak 6 siswa low vision terdiri atas 3 laki-laki dan 3 perempuan, dengan rentang usia 8-10 tahun. Analisis data menggunakan uji-t. Hasil penelitian menunjukkan bahwa inovasi media bola bersuara memiliki pengaruh yang signifikan sebesar 2,05 (α=0.05) terhadap kemampuan orientasi dan mobilitas siswa tunanetra. Simpulan inovasi media bola bersuara membantu meningkatkan kemampuan orientasi dan mobilitas dalam pembelajaran pendidikan jasmani bagi siswa tunanetra.